2016
DOI: 10.1007/s10753-016-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ezetimibe, Simvastatin, and their Combination on Inflammatory Parameters in a Rat Model of Adjuvant-Induced Arthritis

Abstract: Statins are hypocholesterolemic drugs that are prescribed for patients with an increased risk of cardiovascular and cerebrovascular complications. Ezetimibe has an atheroprotective activity through inhibition of the expression of vascular adhesion molecule-I and vascular CD14, a marker of the infiltration of mononuclear leukocytes. Ezetimibe reduces the amount of chemoattractant protein-1 that is available for monocytes and macrophages and alters the activity of nuclear factor κB in leukocytes. The mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…To maximize the efficacy and achieve the greatest statin concentration, 3.0 mg/kg (t.i.d) of Sim was orally administered 3 times/day to the rats in this study, which was equal to 30 mg of drug for a patient in 1 day. Other studies have reported favorable lipid-lowing effects of simvastatin at this concentration [51,52].…”
Section: Discussionmentioning
confidence: 75%
“…To maximize the efficacy and achieve the greatest statin concentration, 3.0 mg/kg (t.i.d) of Sim was orally administered 3 times/day to the rats in this study, which was equal to 30 mg of drug for a patient in 1 day. Other studies have reported favorable lipid-lowing effects of simvastatin at this concentration [51,52].…”
Section: Discussionmentioning
confidence: 75%
“…Statins may exert anti-inflammatory action through inhibition of microglia and astrocytes cells, according to previously described ( Cordle and Landreth, 2005 ; Lindberg et al, 2005 ; Li et al, 2009 ). More precisely, simvastatin have showed its anti-inflammatory properties in different other preclinical studies ( Higuita-Castro et al, 2016 ; Wang et al, 2016 ; Barbosa et al, 2017 ). In addition, Qiu and colleagues ( Qiu et al, 2016 ) showed that simvastatin attenuated neuropathic pain through inhibition of RhoA/LIMK/Cofilin pathway, which is activated after chronic constriction injury and related to actin dynamic regulation ( Qiu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…The beneficial characteristics of statins are not confined to lowering lipids and improvement of dyslipidemia. Statins also have several properties that potentiate them in the respective therapy of different disorders, including anti-inflammatory [ 74 , 75 ], antioxidant [ 76 , 77 ], neuroprotective [ 78 , 79 ], and antitumor [ 80 ]. Consumption of statins has also been related to a decreased rate of Alzheimer's disease and the development of dementia [ 81 ].…”
Section: Statinsmentioning
confidence: 99%